2019
DOI: 10.4034/pboci.2019.191.122
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Effects of Cuminum cyminum Extract Against Enterococcus Faecalis Biofilms From Clinical Isolates

Abstract: Objective: To compare the antibacterial efficacy of Cuminum cyminum (cumin) extract and 2% chlorhexidine. Material and Methods: E. faecalis was isolated from non-vital teeth with chronic apical abscess. Samples were then bred in the ChromAgar medium. Subsequently, E. faecalis bacteria's DNA extraction was performed. DNA was then amplified by conventional PCR, and the product was run on an electrophoresis gel. Subsequently, we extracted Cuminum cyminum seeds using the steam distillation technique. The extract w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…While pure DMSO was often used to prepare stock solutions of test substances, only final exposure concentrations were of interest and were almost always lower than stocks following dilution with bacterial suspensions in media [ [46] , [47] , [48] ] (Supplementary spreadsheet). However, in assays measuring degradation of preformed biofilms whereby test solutions were added to effectively dry, adhered bacterial cells after media was discarded, high (50–100%) final DMSO exposures occurred if stocks were applied undiluted [ 49 , 50 ] ( Table 1 ; Supplementary spreadsheet). Final DMSO exposure concentrations were directly specified or otherwise calculable based on information provided in methods in 66% of articles ( n = 50) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While pure DMSO was often used to prepare stock solutions of test substances, only final exposure concentrations were of interest and were almost always lower than stocks following dilution with bacterial suspensions in media [ [46] , [47] , [48] ] (Supplementary spreadsheet). However, in assays measuring degradation of preformed biofilms whereby test solutions were added to effectively dry, adhered bacterial cells after media was discarded, high (50–100%) final DMSO exposures occurred if stocks were applied undiluted [ 49 , 50 ] ( Table 1 ; Supplementary spreadsheet). Final DMSO exposure concentrations were directly specified or otherwise calculable based on information provided in methods in 66% of articles ( n = 50) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Those that did not include relevant DMSO controls ( n = 38 articles) often used low concentrations (≤1% DMSO) to deliver treatments, which likely contributed to a reduced perceived need for a solvent control [ 47 , [51] , [52] , [53] , [54] , [55] ]. Studies that used higher DMSO concentrations without solvent controls were more concerning [ 49 , 50 , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] ] as were studies that did not provide concentrations of DMSO used in treatments and did not include solvent controls [ 43 , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] ]. Media-only control-treated biofilms were frequently used in the calculations [ 50 , 56 , 57 , 78 , 79 ] although it is most appropriate to compare treatments delivered with DMSO to DMSO-only control-treated biofilms normalised to 100% growth as in [ 41 , [80] , [81] , [82] ].…”
Section: Resultsmentioning
confidence: 99%
“…Controversial data has been found in different studies about the antimicrobial effect of herbal irrigants. Two recent studies showed that cumin essential oil was a more potent antimicrobial agent compared to CHX against all groups of microorganisms [24,25]. Kangabam et al showed that cinnamon extracts can be an effective alternative to NaOCL [26].…”
Section: Discussionmentioning
confidence: 99%
“…Cuminum cyminum also has excellent antifungal [ 20 – 22 ] and analgesic properties [ 23 ]. Two recent studies showed that cumin essential oil was a more potent antimicrobial agent compared to CHX against aerobic bacterial mixture, anaerobic bacterial mixture and E. faecalis and related this antimicrobial activity to the presence of cumin aldehyde and other major components in the composition of this essential oil [ 24 , 25 ]. Kangabam et al showed that, methanol, ethanol, isopropyl alcohol, acetone, and chloroform extracts of Cinnamomum zeylanicum were found to be effective antibacterial agents against E. faecalis—both planktonic cells and 6 weeks biofilm formed on dentin substrate [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The HPLC anlysis of acetonic extract (data not shoun) resulted in the identification of several compounds, among which the most abundant was the p-coumaric acid as the major phenolic acid and diosmin as flavonoid, the apigenines was also detected in cumin extract.These results concur with earlier research, but to a different amounts (Akroum et al, 2010;Bettaieb et al, 2012). Cuminaldehyde is present in high concentrations in the cumin extract (61.65%), Cumene, p-cymene, -pinene, acetic acid, p-cymen-7-ol and terpinene were among other constituents of the extract (Amalia et al, 2019). Tashtoush et al (2016) revealed the presence of gallic, vanillic and chlorogenic acides in cumin seeds.…”
Section: Cumin Extracts Analysismentioning
confidence: 98%